2011
DOI: 10.1002/lpor.201000039
|View full text |Cite
|
Sign up to set email alerts
|

Single quantum dot nanolaser

Abstract: Recent theoretical and experimental progress on nanolasers is reviewed with a focus on the emission properties of devices operating with a few or even an individual semiconductor quantum dot as a gain medium. Concepts underlying the design and operation of these devices, microscopic models describing light-matter interaction and semiconductor effects, as well as recent experimental results and lasing signatures are discussed. In particular, a critical review of the "self-tuned gain" mechanism which gives rise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 218 publications
4
112
0
Order By: Relevance
“…Introduction.-The temporal coherence of a source of radiation is a key quantity that distinguishes laserlike devices from thermal emitters. While the first-order coherence function g (1) (τ ), which is the correlator of field amplitudes at different times, reflects the coherence of the emitted photons, its second-order counterpart g (2) (τ ) involves intensity correlation and gives insights into emission statistics. In conventional semiconductor lasers, which rely on stimulated emission and population inversion, the emission statistics transits from thermal (below lasing threshold) to coherent as revealed by g (2) (τ = 0) = 2 and 1, respectively.…”
mentioning
confidence: 99%
“…Introduction.-The temporal coherence of a source of radiation is a key quantity that distinguishes laserlike devices from thermal emitters. While the first-order coherence function g (1) (τ ), which is the correlator of field amplitudes at different times, reflects the coherence of the emitted photons, its second-order counterpart g (2) (τ ) involves intensity correlation and gives insights into emission statistics. In conventional semiconductor lasers, which rely on stimulated emission and population inversion, the emission statistics transits from thermal (below lasing threshold) to coherent as revealed by g (2) (τ = 0) = 2 and 1, respectively.…”
mentioning
confidence: 99%
“…This simplified form is the one most commonly seen and used in the literature [52] to quantify the cavityenhanced or -inhibited rate of spontaneous emission, relative to the emission in freespace. However, using the emitter-field-reservoir model in the quantum theory of damping, effects ignored in the commonly used Purcell factor expression can be captured.…”
Section: Purcell Effect In Semiconductor Nanolasersmentioning
confidence: 99%
“…As an ultimate microscopic limit of thresholdless semiconductor lasers, single-QD nanolaser, i.e., a single QD coupled to a single mode of an optical cavity shown in Fig. 4, allow us to investigate the light-matter interaction down to the single particle level entering the so-called cavity quantum electrodynamics (QED) regime [4,77,78]. As early as in 1999, Pelton et al [77] firstly proposed a single QD microcavity system as a novel ultralow threshold laser device, consisting of a single InAs/GaAs self-assembled QD coupled to a highfinesse microsphere cavity.…”
Section: Ultimate Nanolasers: Single Quantum Dot Vecsel Devicesmentioning
confidence: 99%
“…As early as in 1999, Pelton et al [77] firstly proposed a single QD microcavity system as a novel ultralow threshold laser device, consisting of a single InAs/GaAs self-assembled QD coupled to a highfinesse microsphere cavity. Later, S. Strauf and co-workers have demonstrated that very few (2-4) QDs as a gain medium are sufficient to realize a photonic crystal (PhC) laser based on a high-quality nanocavity [78]. Photon correlation measurements show a transition from a thermal to a coherent light state proving that lasing action occurs at ultralow thresholds.…”
Section: Ultimate Nanolasers: Single Quantum Dot Vecsel Devicesmentioning
confidence: 99%
See 1 more Smart Citation